Association between antidepressant medication use and steroid dependency in patients with ulcerative colitis: a population-based study. Issue 1 (27th May 2021) - Blackwell, Jonathan; Alexakis, Christopher; Saxena, Sonia; Creese, Hanna; Bottle, Alex; Petersen, Irene; Hotopf, Matthew; Pollok, Richard C G
Abstract : Background: Animal studies indicate a potential protective role of antidepressant medication (ADM) in models of colitis but the effect of their use in humans with ulcerative colitis (UC) remains unclear. Objective: To study the relationship between ADM use and corticosteroid dependency in UC. Design: Using the Clinical Practice Research Datalink we identified patients diagnosed with UC between 2005 and 2016. We grouped patients according to serotonin selective reuptake inhibitor (SSRI) and tricyclic antidepressant (TCA) exposure in the 3 years following diagnosis: 'continuous users', 'intermittent users' and 'non-users'. We used logistic regression to estimate the adjusted risk of corticosteroid dependency between ADM exposure groups. Results: We identified 6373 patients with UC. Five thousand two hundred and thirty (82%) use no ADMs, 627 (10%) were intermittent SSRI users and 282 (4%) were continuous SSRI users, 246 (4%) were intermittent TCA users and 63 (1%) were continuous TCA users. Corticosteroid dependency was more frequent in continuous SSRI and TCA users compared with non-users (19% vs 24% vs 14%, respectively, χ 2 p=0.002). Intermittent SSRI and TCA users had similar risks of developing corticosteroid dependency to non-users (SSRI: OR 1.19, 95% CI 0.95 to 1.50, TCA: OR 1.14, 95% CI 0.78 to 1.66). Continuous users of both SSRIs and TCAs had significantly higher risks of corticosteroid dependency compared with non-users (SSRI: OR 1.62, 95% CI 1.15 to 2.27, TCA: OR 2.02, 95% CI 1.07 to 3.81). Conclusions: Continuous ADM exposure has no protective effect in routine clinical practice in UC and identifies a population of patients requiring more intensive medical therapy. ADM use is a flag for potentially worse clinical outcomes in UC.